تحديد قيم التوتر السطحي لبعض السوائل المستخدمة في عملية غسل الاسنان - ايناس غازي يونس; اياد جياد جرجيس عبدالباقي; منى يوحنا صليوه; عامر عبدالرحمن طاقة (PROSPECTIVE RESEARCHES, 2023)
In this research, the surface tension values of some liquids used to sterilize the teeth were determined from bacteria after drilling and cleaning the teeth from caries. These liquids were respectively (distilled water, chlorine, mouthwash, xylocaine, water solutions - soap and water - washing powder). At concentrations of (1gm-10ml) and (2gm-10ml). The results showed that a soap-water solution with a concentration of (2gm-10ml). It has the lowest surface tension valuen Followed by the ratio of (1gm-10ml) for the same solution. After that comes a waterwashing powder solution with its identical concentrations, respectively Followed by mouthwash (Bio Fresh), chlorine and xylocaine, and finally, distilled water.